Influence of K2NbF7 Catalyst on the Desorption Behavior of LiAlH4 - Ali, Nurul Amirah; Sazelee, Noratiqah; Yahya, Muhammad Syarifuddin; Ismail, Mohammad (Frontiers in Chemistry, 2020)
Modifying the desorption behaviour of LiAlH4 by the addition of K2NbF7 was studied for the first time. The addition of K2NbF7 promotes notable improvement on the desorption behaviour of LiAlH4. Upon the addition of 10 wt.% of K2NbF7, the desorption temperature of LiAlH4 was significantly lowered. The desorption temperature of LiAlH4 + 10 wt.% K2NbF7 sample was lowered to 90 °C (first stage reaction) and 149 °C (second stage reaction). Enhancement of the desorption kinetics performance by LiAlH4 + 10 wt.% K2NbF7 sample was substantiated when the composite sample can greatly desorb hydrogen 30 times faster than pure LiAlH4. Then, with the presence of 10 wt.% K2NbF7, the calculated activation energy value for the first two desorption stages significantly reduced to 80 kJ/mol and 86 kJ/mol; 24 kJ/mol and 26 kJ/mol lower than the as-milled LiAlH4. Analyzing the X-ray diffraction result, it believes that in situ formations of NbF4, LiF and K or K-containing that appeared during the heating process promote the amelioration of the desorption behaviour of LiAlH4 with the addition of K2NbF7.